Predator‐induced changes in dissolved organic carbon dynamics. Issue 3 (23rd October 2018) - Limberger, Romana; Birtel, Julia; Peter, Hannes; Catalán, Núria; da Silva Farias, Daniel; Best, Rebecca J.; Brodersen, Jakob; Bürgmann, Helmut; Matthews, Blake
Abstract : The fate of dissolved organic carbon (DOC) is partly determined by its availability to microbial degradation. Organisms at upper trophic levels could influence the bioavailability of DOC via cascading effects on primary producers and bacteria. Here we experimentally tested whether the presence of fish in aquatic food webs can indirectly affect the composition of the DOC pool. We found that fish had strong positive effects on phytoplankton biomass that affected the dynamics of DOC composition. Specifically, fish increased protein‐like, algae‐derived DOC mid‐experiment, concurrent with the strongest fish‐induced increase in phytoplankton biomass. Fish also increased bacterial abundance, altered the community composition and diversity of bacteria, and temporarily increased DOC compounds with fluorescence properties indicative of microbially‐reprocessed organic matter. Overall, our experiment revealed that fish can positively influence the substrate (algae‐produced DOC) and the key players (bacteria) of the microbial carbon pump. Consequently, fish could contribute to carbon sequestration by stimulating both the production of bioavailable DOC and the microbial degradation of bioavailable to persistent DOC. We propose this as a novel mechanism whereby the loss of predators from global ecosystems could alter carbon cycling.